2016
DOI: 10.1111/ddi.12494
|View full text |Cite
|
Sign up to set email alerts
|

Climate constrains range expansion of an allochronic population of the pine processionary moth

Abstract: Aim Allochronic speciation occurs when sympatric populations sharing similar feeding regimes diverge because they mate at different times. Such speciation mode is fascinating because it permits the study of subsequent adaptations and/or geographic range shifts undergone by the populations that face new ecological constraints. Moreover, exploring whether intraspecific differentiation is accompanied by niche divergence is crucial for planning efficient biodiversity management and invasive species control. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 62 publications
(123 reference statements)
1
23
0
Order By: Relevance
“…In a recent study, Godefroid et al. () showed that the current distribution of the LSP is limited by the high summer temperature occurring elsewhere in Portugal, even though larvae of this population were proved to cope better with higher temperatures than larvae of Portuguese and French WPs (Santos, Paiva, et al., ). In the first steps of the differentiation, milder environmental conditions could have favoured the success of the diverging population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Godefroid et al. () showed that the current distribution of the LSP is limited by the high summer temperature occurring elsewhere in Portugal, even though larvae of this population were proved to cope better with higher temperatures than larvae of Portuguese and French WPs (Santos, Paiva, et al., ). In the first steps of the differentiation, milder environmental conditions could have favoured the success of the diverging population.…”
Section: Discussionmentioning
confidence: 99%
“…This unique shifted population is known as the “summer population” (SP) as opposed to all other known populations that are referred to as “winter populations” (WPs), in relation to the development time of the conspicuous larvae. The SP was initially restricted to a small area of the Mata Nacional and has been slowly expanding along the coast since then (Godefroid et al., ). Strikingly, all larval stages of the SP develop under radically different environmental conditions compared to the typical WPs, experiencing much higher temperatures that were so far supposed to be lethal to early larval stages (Huchon & Démolin, ; Santos, Paiva, Tavares, Kerdelhué, & Branco, ).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of refugia has always been challenging [ 5 , 9 ]. Responses of species to climatic changes may be different due to their unique biology and historical distributions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Godefroid et al. () modelled the potential distribution of the summer populations, and found its current distribution to be restricted to coastal areas due to unsuitable climate inland, despite their adaptations to higher temperatures (Santos, Paiva, et al., ; see above). Predicted increases in temperature within their current range could be detrimental to the survival of the summer population (Godefroid et al., ).…”
Section: Discussion and Synthesismentioning
confidence: 99%